Pediatricians’ Role in Oral Health of Children - Sharma, Abhishek; Parkar, Sujal; Sudheer, H; Thanveer, K; Ajithkrishnan, CG (Journal of Orofacial Research, 2014)
Objective: To evaluate the knowledge, attitude and practices of pediatricians toward oral health of children in Vadodara city. Materials and methods: All9 73 pediatricians registered in Indian Medical Association were included in the study. A closeended questionnaire consisting of 22 questions was administered personally. The data obtained was subjected to statistical analysis using SPSS 14.0 version. Factor analysis (principal component analysis) was carried out to know the variation in knowledge of risk factors for oral diseases. Results: Response rate was 82%. Most of them had knowledge of dental caries (100%), malocclusion (93%), gingivitis (90%) and periapical abscess (81%). Contributing risk factors according to pediatricians knowledge (calculated by factor analysis) was found to be 65% with sugar products, followed by 37% with bottle-feeding, 30% with harmful oral habits and 23% with oral hygiene practices. All pediatricians considered that oral health and primary teeth are of importance and in accordance majority of them counseled parents regarding sugar consumption and oral hygiene practices. Conclusion: Majority of pediatricians had acceptable level of knowledge regarding common dental diseases of children. Their attitude and practices of oral health was found satisfactory.